DESIGN OF LINEMANTOOLS WITH VOLTAGE DETECTOR - Ahmad Ridowi; Dody Wahjudi; Tri Watiningsih (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2019)
PLN officers often experience obstacles in placing equipment and materials when working on poles. Toovercome this problem, officers use ropes, carabiners, and safety belts or safety belts there are specialplaces to put the equipment, but the existing equipment has many shortcomings, namely difficulty in placingand retrieving equipment and constrained in movement or maneuvering. This can cause the equipment ormaterial to fall, thus endangering the staff underneath and causing loss due to damage to the tool or theenvironment.In order to achieve K2 (Electricity Safety) and K3 (Occupational Safety and Health) and maintain company image, in overcoming this problem, a tool called